Language Use in Deaf Children With Early-Signing Versus Late-Signing Deaf Parents - Sümer, Beyza; Özyürek, Aslı (Frontiers in Communication, 2022)
Previous research has shown that spatial language is sensitive to the effects of delayed language exposure. Locative encodings of late-signing deaf adults varied from those of early-signing deaf adults in the preferred types of linguistic forms. In the current study, we investigated whether such differences would be found in spatial language use of deaf children with deaf parents who are either early or late signers of Turkish Sign Language (TİD). We analyzed locative encodings elicited from these two groups of deaf children for the use of different linguistic forms and the types of classifier handshapes. Our findings revealed differences between these two groups of deaf children in their preferred types of linguistic forms, which showed parallels to differences between late versus early deaf adult signers as reported by earlier studies. Deaf children in the current study, however, were similar to each other in the type of classifier handshapes that they used in their classifier constructions. Our findings have implications for expanding current knowledge on to what extent variation in language input (i.e., from early vs. late deaf signers) is reflected in children’s productions as well as the role of linguistic input on language development in general.